Analysis of Body Fluid Distribution, Phase Angle and Its Association With Maximal Oxygen Consumption in Facioscapulohumeral Dystrophy: An Observational Study - Oscar Crisafulli; Renato Baptista; Patrik Drid; Luca Grattarola; Giorgio Bottoni; Emanuela Lavaselli; Massimo Negro; Rossella Tupler; Venere Quintiero; Giuseppe D'Antona (Health Science Reports)
ABSTRACT Background and Aims Body composition parameters associated with aerobic fitness, mirrored by maximal oxygen consumption (V̇O2max), have recently gained interest as indicators of physical efficiency in facioscapulohumeral dystrophy (FSHD). Bioimpedance analysis (BIA) allows a noninvasive and repeatable estimate of body composition but is based on the use of predictive equations which, if used in cohorts with different characteristics from those for which the equation was originally formulated, could give biased results. Instead, the phase angle (PhA), a BIA raw bioelectrical parameter reflecting body fluids distribution, could provide reliable data for such analysis. Methods 33 clinically and genetically characterized FSHD patients (mean age 35.7; 10 females) and 27 sex and age‐matched healthy controls (HC) were included in the analysis. BIA was used to evaluate body fluids distribution (intracellular water [ICW], extracellular water [ECW], and total body water [TBW]), and PhA, while cardiopulmonary exercise test was used to estimate V̇O2max. Results The groups were comparable for ECW and TBW. Instead, patients showed lower values of ICW (p = 0.020), ICW/ECW ratio (p < 0.001), and PhA (p < 0.001). Moreover, patients reported lower V̇O2max (p = 0.001 for absolute values; p = 0.002 for values expressed in relation to body weight) which, unlike HC, was not associated to PhA. Conclusion Based on our results, PhA of FSHD patients is lower than HC. Since PhA mirrors the ICW/ECW ratio, the lower share of ICW seems to be the basis of such difference. Given the lack of association with V̇O2max, PhA cannot be considered a reliable indicator of aerobic fitness in FSHD.